Análise crítica à aplicação de selos de sustentabilidade como estratégia de redução de emissões de CO2 na construção civil - Vons, Michele Cristina (2024)
Due to the high rates of construction material waste, along with significant energy consumption in the construction industry, sustainability has gained attention in this sector. The creation of certifying bodies and sustainable performance evaluators for projects, buildings, and renovations aims to guide actions that reduce environmental, social, and economic impacts. In Brazil, international certification systems such as LEED, AQUA-HQE, and BREEAM stand out. However, despite being internationally recognized, these certifications are not adapted to the Brazilian reality. This occurs due to differences in construction methods, climatic conditions, building materials, and operational management used in Brazil compared to construction practices in North America and Europe. In this context, Youth Centers are public spaces aimed at youth development, where the application of sustainability strategies in civil construction can foster awareness of this issue among young people. Thus, the methodology adopted in this study consists of a qualitative and quantitative analysis of the Youth Center in the city of Cascavel-PR, conducted through an evaluation of the building's quality and adherence to aspects required for certification in the various systems analyzed. Data on the target audience, activities, and infrastructure were gathered through visits and document consultation. Following this, a critical study was conducted on the application of the sustainability seal requirements for schools, in order to verify whether these requirements fit the Brazilian reality or identify necessary adaptations. The goal was to determine the changes needed in the Youth Center to classify it as a sustainable building and propose solutions to make it an example of sustainable educational construction and the adaptation of international seals to the national context. Finally, a quantitative analysis of emissions, based on the primary construction materials used in the Youth Center, was carried out. The research results showed that the comparison between traditional masonry, Steel Frame, and Wood Frame construction methods reveals significant differences in carbon dioxide CO₂ emissions. Studies indicate that the Steel Frame system emits less CO₂ compared to traditional masonry, due to the reduced use of heavy materials and the use of galvanized steel, which, despite having a considerable carbon footprint during production, results in a lighter and more efficient structure. On the other hand, Wood Frame, which primarily uses wood, also shows reduced emissions, especially when considering the carbon sequestration provided by the wood during its growth. Therefore, in terms of CO₂ emissions, the Steel Frame stands out as the most sustainable option, followed by the Wood Frame, while traditional masonry tends to generate the highest emissions, mainly due to the intensive use of cement and concrete in its construction. This demystifies the notion that the case study building is sustainable, as its structure is made of traditional masonry.